PSYCHO-SOCIOLOGICAL FACTORS AS PREDICTORS OF COUNTERPRODUCTIVE WORK BEHAVIOUR AMONG THE NON-ACADEMIC STAFF OF UNIVERSITIES IN SOUTHWESTESTERN NIGERIA (2014)
Counter-productive Work Behaviours (CWB) are acts of employees going against the expectations of an organisation. This behaviour is on the increase in the Nigerian university system particularly among non-academic staff, with negative consequences on the system. Literature has documented the effects of CWB without its pre-disposing factors in the university system. The study, therefore, investigated the predictive effects of psychological (Locus of Control (LoC), impulsiveness, anxiety, conscientiousness, agreeableness, neuroticism, openness to experience, extroversion) and sociological factors (age, gender, marital status, educational qualification and workers‘ income) on CWB among non-academic staff of universities in Southwestern Nigeria. The descriptive survey research design of the ex-post facto type was adopted. Stratified random and proportionate sampling techniques were used to select 1,442 non-academic staff in six purposely selected universities (three federal, two state and one private) in Southwestern Nigeria (751 senior non-academic staff, 691 junior non-academic staff). The research instruments used were: Demographic Information Questionnaire, conscientiousness (r = 0.78), agreeableness (r = 0.76), openness (r = 0.83), extroversion (r = 0.91), LoC (r=0.82). Impulsivity Measure (r=0.56), Neuroticism Scale (r=0.70) and Anxiety Scale (r=0.72). Nine research questions were answered and six hypotheses tested at the 0.05 level of significance. Data were analysed using Pearson product moment correlation and multiple regression. The participants were 786 male and 656 female with age of 46.5 ± 8.08. There was an observed difference in the level of CWB in universities sampled: state-owned (64.0%), federal (41.2%) and private (39.8%). Psycho-sociological factors significantly predicted CWB (F (13,1428) = 20.06); and jointly contributed 15.4% to CWB variance. Psychological factors (F (8,1433) = 31.41) jointly contributed to CWB, accounting for 14.9% in its variance, while the joint sociological factors did not. Conscientiousness (β=.198), LoC (β = -.19) agreeableness (β = -.18), neuroticism (β=.07), openness to experience (β=.07), extroversion (β=-.14), impulsivity measure (β= -.02) anxiety (β =.15) and marital status (β = -.09) contributed relatively to CWB but impulsivity measure, qualification and income did not. Locus of control (r = -.170), conscientiousness (r= .156); agreeableness (r= .23), neuroticism (r = 0.83); openness (r = -.14), extroversion (r = -22); impulsivity measure (r= .036) anxiety scale (r = .21) correlated significantly CWB. The psycho-sociological factors helped to negatively predict CWB among non-academic staff in Southwestern Nigerian universities. Marital status, locus of control, conscientiousness, agreeableness, neuroticism, openness to experience, extroversion and anxiety had great influence on counter-productivity work behaviours of non-academic staff in Southwestern Nigerian universities. These factors should be considered by counseling psychologists when designing intervention strategies to minimize counter-productivity work behaviours among the non-academic staff. Keywords: Nigerian universities non-academic staff, Counter-productive work behaviour, Big Five personality factors. Word count: 421